A Systematic Approach to Spanish Neuropsychological Evaluation: Case Report with a Mexican Woman in an Outpatient Setting. (30th August 2019) - Rivera, P; Savage, K; Ball, A
Abstract: Objective: The following case will demonstrate a systematic approach to neuropsychological evaluation with Spanish-speaking individuals, which includes creating a suitable test battery, interpreting results with appropriate normative samples, and incorporating personal history. Case Description: 61-year-old, right-handed, Mexican female with 2 years of formal education, and with a recent history of subarachnoid hemorrhage with hydrocephalus. She was referred by her social worker and primary care provider to discern whether the reported cognitive complaints were due to a neurocognitive condition or depression. Diagnostic Impressions and Outcomes: The evaluation was administered entirely in Spanish and some exams were modified to accommodate her limited literacy skills. She exhibited deficits in executive functioning, verbal fluency, and memory. Emotional testing revealed moderate depression with anxious distress, which she attributed to significant changes in everyday life. Her family informed us that she was the "matriarch of the family" and worked as a farm field truck driver, with significant difficulties/lack of engagement in both of these roles. Therefore, diagnoses of probable major vascular neurocognitive disorder and major depressive disorder with anxious distress were assigned. With this information, her providers were able to connect the family with community resources. Discussion: The Hispanic population continues to be the fastest growing demographic in the United States. As more clinicians will work with members of this ethnicity in outpatient settings, it is important that they incorporate culturally-relevant factors in their approach to testing and interpretation of results. Nonetheless, this case demonstrates the current challenges and limitations, including modification of exams, differences in educational system that underlie test construction, and patient's history. Recommendations for future areas of study and practice will also be discussed.